A Comparative Study of Cocoa Beans in Indonesia, Ghana, Côte d’Ivoire, Ecuador, and Cameroon Using the RCA, RSCA, and MSI Approaches - Dermawan, Denden Dimas; Saputera, Denny (Golden Ratio of Mapping Idea and Literature Format, 2026)
This study analyzes the competitiveness of cocoa bean exports from Indonesia, Ghana, Côte d’Ivoire, Ecuador, and Cameroon using the Revealed Comparative Advantage (RCA), Revealed Symmetric Comparative Advantage (RSCA), and Market Share Index (MSI) approaches. Secondary data from 2014 to 2023 were collected from FAO, BPS, UN Comtrade, and Trade Map. The results show that Indonesia experienced a decline in cocoa production from 734,795 tons in 2019 to 641,741 tons in 2023, while export volume decreased by more than 70% over the same period. RCA and RSCA indices confirm that Indonesia lost its comparative advantage, with RCA values falling below one and RSCA remaining negative since 2017. In contrast, Côte d’Ivoire and Ghana consistently recorded strong competitiveness, supported by favorable policies and high productivity. Ecuador showed gradual improvement, while Cameroon’s performance fluctuated due to domestic instability. MSI results reveal that Indonesia’s global market share fell from 1.96% in 2014 to only 0.15% in 2023. These findings suggest that Indonesia needs to strengthen its downstream cocoa industry, enhance farm productivity, and improve policy support to regain competitiveness. The study contributes to the literature by providing a multi-country comparison of cocoa competitiveness using three quantitative indices and highlights practical implications for policymakers and industry stakeholders.